Methodologies for Large-Size Pouch Lithium-Ion Batteries End-of-Life Gateway Detection in the Second-Life Application. Issue 16 (17th December 2020) - Attidekou, Pierrot S.; Milojevic, Zoran; Muhammad, Musbahu; Ahmeid, Mohamed; Lambert, Simon; Das, Prodip K.
Abstract : In electric vehicles, the battery pack is deemed to reach the end-of-life (EoL) when the capacity of the lithium-ion batteries (LiBs) drops below 80% of their nominal capacity. This leads to an emerging market of reuse and repurposing of retired LiBs in less power demanding applications. However, longevity, safety, higher performance and system warranty are the requirements of such a novel market and detecting batteries degradation level and their "real" EoL in the second-life applications before recycling is paramount. Here, we present a combination of diagnosis methodologies applied on large-size pouch LiBs from a dismantled first-generation Nissan Leaf retired battery pack, cycled with different accelerated ageing cycling procedures. While the capacity-based state of health is limited, the degradation modes and the "real" EoL were successfully detected by the incremental capacity analysis (ICA) and infrared (IR) thermal techniques. The ICA and IR measurements can be utilised to detect quantitative changes or different qualitative spacious non-uniform ageing changes over the large-size LiB's surface. Moreover, these methodologies represent an important first step for "real" EoL prediction a hundred cycles earlier and can be applied on large-size pouch cells with different chemistries in second-life applications.